1871 Productivity Differentials and the Decline of the Maritime Manufacturing Sector - Chernoff, Alex (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2014)
This article examines manufacturing productivity differences between urban centres in the Maritimes and Central Canada. The results indicate that productivity in the Maritime cities exceeded that of its Central Canadian counterparts. The article reconciles this finding with earlier research by demonstrating that the relative productivity of the Maritimes at the provincial level is lowered by the higher proportion of rural establishments with low productivity in the region. The article concludes that lower productivity in the rural regions of the Maritimes may have contributed to the decline of the Maritime manufacturing sector.